Teaching Materials Development of Bilingual Drawing North Sumatra Ornamental Variety to Improve Tourism Souvenirs Design at Universitas Negeri Medan - Daulat Saragi; Nelson Tarigan (RIRAI Publisher, 2023)
The results of the analysis of the needs of students and lecturers in the archipelago ornamental design courses in the Department of Fine Arts Education were found that there was still a lack of teaching materials for the course. As a result, students are less familiar with and apply a variety of ornamental North Sumatra to other courses such as tourist souvenir designs, batik courses and others that require typical North Sumatra ornamentist. Research Objectives To develop and apply the textbook according to the needs of students so that they are with the needs of students, the textbook designed entitled Drawing North Sumatra Ornamental Variety in the form of two languages, Indonesian and English. Research and development conducted with five stages referring to the Addie model developed by Robert M. Branch. Products developed are validated by 3 experts in their fields and each concluded very well and is suitable for use. This proves that the teaching material for drawing a variety of North Sumatra has used by art students and for the public is suitable for use and effective. After conducting product trials to students, it was found that the product developed was very helpful for students and also had an impact on the level of creativity of students designing a variety of souvenirs based on local ornaments of North Sumatra. The results of the study can increase student activities and safety and contribute to improving student achievement in the design of ornamentists in tourist and other art objects. KEYWORDS